A retrospective study on the efficacy and safety of Envafolimab, a PD-L1 inhibitor, in the treatment of advanced malignant solid tumors - Zhang, Congjun; Li, Jingjing; Wu, Hongyang; Huang, Wei; Da, Liangshan; Shen, Yuanyuan; Sun, Guoping (Frontiers in Pharmacology, 2024)
Envafolimab, a PD-L1 inhibitor, has demonstrated potential in treating advanced malignant solid tumors (AMST). To study its’ efficacy and safety in AMST, our retrospective study recruited 64 patients with various AMST, and treated with Envafolimab (400 mg every three weeks). We divided the patients into two cohorts: Cohort 1 (25 patients) receiving Envafolimab as first-line therapy, and Cohort 2 (39 patients) receiving it as second-line or subsequent therapy. Our analysis focused on Envafolimab’s efficacy and safety. Over a median follow-up of 7.1 months, Cohort I reported a Disease Control Rate (DCR) of 72.0% and an Overall Response Rate (ORR) of 12.0%, while Cohort II had a DCR of 51.3% and an ORR of 5.1%. Notably, patients with more than four treatment cycles showed higher DCR and longer Progression-Free Survival (PFS) than those with fewer cycles. Adverse events were observed in 68.8% of patients, with severe events (CTCAE grade 3/4) in 14.1%. Most adverse events were mild, leading to treatment discontinuation in only 3.1% of patients, with no life-threatening events reported. In summary, Envafolimab is a safe and effective treatment for AMST, in both initial and later therapy stages, particularly with extended treatment duration, meriting further clinical trials.